On the nature of deferred income taxes* - CHEUNG, JOSEPH K. (Contemporary Accounting Research, 1989)
Abstract. The topic of deferred income taxes has generated considerable controversy. This paper observes that much of this controversy centers on the contingent nature of income taxes. It reviews the similarity between the firm's income tax liabilities and a European call option written on the firm's pretax value. From this perspective, deferred taxes are shown to effectively alter the exercise price of the call option held by the government, thus affecting the value of the firm's debt and equity claims. Additional results are obtained from the model by valuing the tax liabilities and the firm's financial claims via an exact option pricing formula. Finally, the paper shows that the model is robust to some of its underlying assumptions. Résumé. Les impôts sur le revenu reportés ont été l'objet d'une immense contraverse. L'auteur fait remarquer que cette controverse est en grande partie centrée sur la nature conjoncturelle des impôts sur le revenu. Il examine la similarité entre la dette fiscale de l'entreprise et une option d'achat européenne libellée sur la valeur avant impôt de l'entre‐prise. Dans cette perspective, l'auteur démontre que les impôts reportés modifient effectivement le prix d'exercice de l'option d'achat détenue par le gouvernement, infiuant ainsi sur la valeur des droits à l'actif de l'entreprise. Il obtient des résultats supplémentaires du modèle en évaluant la dette fiscale et les créances financières de l'entreprise par l'intermédiaire d'une formule de détermination du prix exact de l'option. Enfin, l'auteur démontre que certaines des hypothèses sous‐jacentes au modèle résistent à l'analyse.